Fostering Institutional and Cultural Change Through the Australian Network of University Science Educators : 'SaMnet' : Final Report. - Sharma, Manjula; Rifkin, Will; Johnson, Elizabeth; Tzioumis, Vicky; Hill, Matthew (Office for Learning and Teaching, 2014)
Final report from a project that aimed to improve teaching in science and mathematics by developing 100 (transformational) leaders among academics, associate deans (education), and academic staff developers. They engaged in twenty-five action-learning projects, working with heads of school to foster change in pedagogy. Their efforts were supported by evidence from communities of practice in the scholarship of teaching and learning (SoTL) formed to focus on four areas of need, or themes, identified by consensus across a new national network of science and mathematics educators. The network built on existing disciplinary and regional ties and drew on the constituency for the eighteen-year old national conference on university science and mathematics education. Network members collaboratively liaised with Deputy Vice-Chancellors (Academic) to identify, develop, and publicise modes of refereed SoTL publication to enable network members to advance within the traditional reward structures of science.